Preventive effect of Trimetazidine on contrast induced Acute Kidney Injury in patients with chronic kidney disease undergoing coronary angiography and angioplasty - اسماعيل, كنان; إياس الخير; عبد الفتاح عباس (Latakia University Journal -Medical Sciences Series, 2024)
Background: Contrast induced Acute Kidney Injury (CI-AKI) may be defined as Acute Renal Failure (ARF) that occurs within 24-72 hours of exposure to intra-venous or intra-arterial iodinated contrast media that cannot be attributed to other causes. CI-AKI occurs in up to 5% of hospitalized patients with normal renal function prior to injection of contrast media. It occurs more frequently in patients with renal impairment particularly if associated with diabetic nephropathy. Among all procedures utilizing contrast agents for either diagnostic or therapeutic purposes, coronary angiography and percutaneous coronary interventions are associated with the highest rates of CI-AKI. Trimetazidine has been described as a cellular anti-ischemic agent. Previous studies demonstrated that Trimetazidine prevents the deleterious effects of ischemia-reperfusion at both the cellular and mitochondrial levels and exerts an anti-oxidant effect. It inhibits excess release of oxygen free radicals, limits cellular acidosis, protects Adenosine Triphosphate (ATP) stores, reduces membrane lipid peroxidation and inhibits neutrophil infiltration. Aim: to determine if adding TMZ to standard hydration therapy consistently reduces CI-AKI in patients with chronic kidney disease undergoing coronary angiography CAG and angioplasty Methods and Results: This study was conducted on 94 patients having a eGFR between 89 and 30 ml/min and presenting for coronary angiography procedures. The patients were divided into two equal groups each including 47 patients where both groups received parenteral hydration in the form of isotonic saline at a rate of 1 mg/kg body weight per hour starting 12 hours before angiography and up to 12 hours thereafter. In Group 1, patients received additional medication in the form of trimetazidine 35 mg po twice daily for 72 hours and starting 48 hours before the procedure which was not received in group 2 (control). There was a significant difference regarding the rate of CI-AKI among TMZ versus control groups (8.5% vs 23.4%). Conclusion: Administration of trimetazidine in a dose of 35mg twice daily orally in conjunction with standard early saline hydration is an effective method to prevent or reduce the incidence of contrast-induced Acute Kidney Injury following the administration of contrast media during coronary angiography procedures in patients with mild-moderate basal renal insufficiency.